E-Planner: A web-based tool for planning environmental enhancement on British agricultural land. (September 2022) - Redhead, John W.; Burkmar, Richard; Brown, Mike; Pywell, Richard F.
Abstract: E-Planner is a free, web-based, application which provides land managers with fine-scale maps of the suitability of agricultural land in Great Britain for environmental enhancement. E-Planner is designed to streamline decision-making around the choice and spatial targeting of environmental management interventions. Suitability scores are calculated by integrating a range of biophysical data sets and presented as easy-to-interpret maps, at fine resolutions (5 m) equivalent to those used by precision agriculture technology. The information provided by E-Planner is important for landscape-to field-scale spatial targeting of farm management to maximise the efficiency of both crop production and environmental delivery. Whilst many datasets and tools support the former, equivalents for environmental factors are not widely available. The methods used by E-Planner for collating and presenting data on environmental constraints and drivers are widely applicable, and efficient spatial targeting of agronomic and environmental management forms an essential step towards sustainable agriculture, a global issue. Highlights: E-Planner is a free, web-based, agricultural decision support tool for GB. E-Planner is designed to support and streamline agri-environmental decision-making. The tool presents maps of suitability for different environmental opportunities. Maps are at fine resolutions (5 m) equivalent to precision agricultural data. Suitability scores show good agreement with expert field validation.